Hydrogen-bonded quasi-layered polypyrrole-tungstate complex with exceptional electrochemical capacitance over 25000 cycles. (1st June 2022) - Liu, Huabo; Xiao, Kefeng; Yu, Mengying; Zhang, Qingran; Wang, Da-Wei
Abstract: Miniaturised and compact energy storage systems are critical for the development of modern electronic products. Here, we report a novel conductive polypyrrole-tungstate self-assembly with quasi-layered structure (denoted tungstate anion linked polypyrrole or TALPy) and its performance for use as high-density and ultra-thick electrodes in supercapacitors. The TALPy electrodes exhibit good charge storage kinetics, excellent volumetric and areal capacitances. With an ultrahigh mass loading of 50 mg cm −2, TALPy electrode delivers a highest areal capacitance of 4.12 F cm −2 (at 1 mA cm −2 ), surpassing many state-of-the-art electrode materials. More importantly, TALPy electrode also shows a remarkable stability with 94% of capacitance retention after 25, 000 charge/discharge cycles, which surpasses numerous polymer-based electrodes. Graphical abstract: A polypyrrole-tungstate hydrogen-bonded complex shows exceptional areal capacitance as well as excellent cycling stability. Image 1 Highlights: Highlights of this work: Synthesis of a polypyrrole-based complex with quasi-layered structure Identification of hydrogen-bonding in this tungstate-polypyrrole complex Demonstration of exceptional cycling stability of this material Achievement of high areal capacitance of this polypyrrole-tungstate complex